Banners, buntings, garlands & pennants : 40 creative ideas using paper, fabric & more - Sheldon, Kathy, 1959-; Carestio, Amanda (Lark, 2016)
"Festive and eye-catching, banners, buntings, garlands, and pennants add visual fun to almost any type of celebration or space. These 40 quick and easy projects-- made of paper, fabric, felt, and more-- make beautiful displays. Use them for special events, for holidays, when entertaining, or even just to spice up a room. A basics section gives beginners a primer on the materials and techniques they need"--